High-Performance Liquid Chromatographic Quantification of Rifampicin in Human Plasma: Method for Therapeutic Drug Monitoring: Therapeutic Drug Monitoring of Rifampicin - Sameh, Trabelsi; Hanene, Eljebari; Rim, Charfi; Issam, Salouage; Emna, Gai'es; Jebabli, Nadia; Mohamed, Lakhal; Anis, Klouz (Biological Sciences - PJSIR, 2013)